2004
DOI: 10.1002/ps.896
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of resistance to carpropamid in Magnaporthe grisea

Abstract: The inhibitory activity of carpropamid on scytalone dehydratase (SDH) extracted from a carpropamid-resistant strain of Magnaporthe grisea (Hebert) Barr was dramatically reduced in comparison with that on SDH extracted from the sensitive strain. A single-point mutation (G to A) located at the upstream region (233 bp downstream from the ATG codon) resulting in a one-amino-acid substitution (valine [GTG] 75 to methionine [ATG]: V75M) was found in the resistant strain. To examine whether the V75M mutation is the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 24 publications
(25 reference statements)
0
34
0
2
Order By: Relevance
“…demonstrated that 1 and 10 µg a.i./mL of carpropamid did not have efficacy in control-resistant isolates of M. oryzae in the greenhouse. 25) Although several reports demonstrated that the carpropamid-resistant isolates of M. oryzae had been detected in fields, 24,25,27,39) the M. oryzae isolates from Taiwan still showed sensitivity to carpropamid. In addition, certain researchers indicated that using mycelial melanization also could be helpful to compare the sensitivity of M. oryzae isolates to tricyclazole 28) and carpropamid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that 1 and 10 µg a.i./mL of carpropamid did not have efficacy in control-resistant isolates of M. oryzae in the greenhouse. 25) Although several reports demonstrated that the carpropamid-resistant isolates of M. oryzae had been detected in fields, 24,25,27,39) the M. oryzae isolates from Taiwan still showed sensitivity to carpropamid. In addition, certain researchers indicated that using mycelial melanization also could be helpful to compare the sensitivity of M. oryzae isolates to tricyclazole 28) and carpropamid.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27] Moreover, certain reports indicated that the decreased efficacy of carpropamid against rice blast in Saga Prefecture in Japan was due to point mutation at codon 75 (GTG→ ATG) in the scytalone dehydratase (SDH) gene and the amino acid valine changing into methionine. 24,25) However, the tricyclazole-resistant isolate still could not be detected in a natural field and the mechanism of tricyclazole resistance generated by UV radiation is still not clear. 28) Strobilurins are new fungicides that can inhibit electron transference of cytochrome b to c at complex III in mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…Kaku et al (2003), reported resistance to carpropamid (Melanin Biosynthesis Inhibitors (Dehydratase) (MBI-D)) with altered target site (scytalone dehydratase) as possible mechanism of resistance. Resistance to carpropamid was confirmed in the strains of Magnaporthe grisea due to V75M mutation that causes low sensitivities of SDHs of the carpropamid -resistant strains, and strongly suggests that the V75M mutation confers resistance of these strains to carpropamid (Takagaki et al, 2004).…”
Section: Fungicide Resistancementioning
confidence: 91%
“…8,9) Studies on the mechanism of resistance and characterization of mutant STD proved that a single-point mutation resulted in a one-amino acid substitution (valine [GTG] 75 to methionine [ATG]: V75M) in STD. 10,11) Recently, new STD-inhibitors such as diclocymet 12) and fenoxanil 13) have been developed and registered as anti-blast chemi-cals in Japan. They are considered to have action mechanisms similar to carpropamid.…”
Section: Reviewmentioning
confidence: 99%